(untitled) (Journal of Pharma Insights and Research, 2025)
A natural mosquito repellent cream was formulated using neem oil (Azadirachta indica) as the primary active ingredient to address the growing concerns over synthetic repellent toxicity and environmental impact. Five formulations were developed using varying concentrations of neem oil, coconut oil, vitamin E, beeswax, and rose oil. Physicochemical evaluation including pH measurement, spreadability, stability testing, irritancy studies, and antimicrobial assessment were carried out. Among the formulations, F2 exhibited optimal characteristics with a skin-compatible pH of 5.5, superior spreadability, and reasonable stability at room temperature. The cream showed moderate mosquito repellency with complete protection for approximately 2 hours, significantly shorter than the 5.2 hours provided by a 15% DEET formulation tested under identical conditions. The F2 formulation maintained 78.3% protection at 2-3 hours post-application, declining to 52.6% at 3-4 hours, necessitating reapplication every 2-3 hours for continued effectiveness. Stability studies revealed a 15% degradation of azadirachtin content after 90 days at room temperature, with accelerated degradation (28% loss) and phase separation observed at elevated temperatures (45°C). The complex repellent mechanism likely involves modulation of multiple chemosensory pathways in mosquitoes, including inhibition of specific odorant receptors involved in host recognition. While this formulation is a promising eco-friendly alternative to synthetic repellents, its shorter protection duration and limited thermal stability highlight the need for developing advanced controlled-release systems to enhance the practical utility of these natural ingredients in mosquito control programs.